Pendidikan Dini Prinsip Edukasi Kesehatan Gizi Seimbang melalui metode Kids Play and Care - Salmon Charles Siahaan; Natalia Yuwono (Universitas Andi Djemma, 2021)
Balanced nutrition is a series of nutritional consumption in a balanced, varied and appropriate amount to the body’s needs, and paying attention to physical activity for at least 30 minutes every day, having a clean lifestyle, monitoring body weight regularly and drinking 8 glasses of water a day. Education on Balanced nutrition from an early age is primelytoincrease awareness about the importance of eating foods with a variety of nutrients and physical activity as an effort to maintain personal and physical health. This community service aims to foster a habit of eating nutritious food and living a clean and hygienic life such as washing hands six steps before eating to prevent disease transmission. Implementation method with two-way discussion so that it can trigger the activeness of students. Students who are active and get the most scores will get rewards. Counseling on balanced nutrition to elementary school children went well, all participants were enthusiastic in participating in this activity